Pelatihan Manajemen Keuangan dan Administrasi BUMDES untuk peningkatan daya saing BUMDES ( Badan Usaha Milik Desa ) Menuju Desa Mandiri pada BUMDES Puloniti, Kabupaten Mojokerto - Ratnawati, Dyah; Syaiful Akbar, Fajar; Khanida, Marisha (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
The development of the economic world in Indonesia in general, in Mojokerto in particular, has made various business actors compete in improving the performance of their companies through product competitiveness and improving the company's operational systems themselves, based on research conducted by the UNIM Accounting Study Program Community Service Team in collaboration with the UPN Accounting Service Team